2011
DOI: 10.1007/s00261-011-9824-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignancy in crossed fused ectopic kidney

Abstract: Crossed fused ectopia of kidneys is a rare congenital anomaly. It is usually associated with congenital anomalies of the gut. Development of malignancy in crossed fused ectopic kidney is uncommon. We present two cases, both females aged 47 and 60 years with crossed fused renal ectopia detected due to the development of malignancy in them. This report highlights the rare occurrence of the entity and role of US, CT scan and MRI in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…There are reported cases of renal cell carcinoma, squamous cell carcinoma of renal pelvis origin, Wilm's tumor, and adenocarcinoma associated with crossed fused renal ectopia (Cook and Stephens 1977a, b;Redman and Beryl 1997;Aquilera Tubet et al 2005). A lump in the lower abdomen and painless hematuria are signs of malignant involvement of an ectopic kidney (Soni et al 2012). Associations with the absence of the vas deferens, cryptorchidism, and skeletal abnormalities have been reported.…”
Section: Associated Anomaliesmentioning
confidence: 96%
“…There are reported cases of renal cell carcinoma, squamous cell carcinoma of renal pelvis origin, Wilm's tumor, and adenocarcinoma associated with crossed fused renal ectopia (Cook and Stephens 1977a, b;Redman and Beryl 1997;Aquilera Tubet et al 2005). A lump in the lower abdomen and painless hematuria are signs of malignant involvement of an ectopic kidney (Soni et al 2012). Associations with the absence of the vas deferens, cryptorchidism, and skeletal abnormalities have been reported.…”
Section: Associated Anomaliesmentioning
confidence: 96%
“…However, the association between MDAs and uterine or renal cancer remains relatively unexplored in the literature. To date, only 32 cases of uterus didelphys complicated by endometrial carcinoma have been reported, and three cases of MDAs combined with renal cancer have been documented [2][3][4]. In this manuscript, we present a unique case of uterus didelphys with concurrent endometrial cancer in a patient who had previously undergone treatment for clear cell renal carcinoma eight months prior.…”
Section: Introductionmentioning
confidence: 92%
“…It is hypothesized to be associated with caudal rotation of the embryo, which is supported by increased prevalence in patients with scoliosis. 5 Associated conditions include vertebral defects, anal atresia, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities (VACTERL), various urogenital abnormalities, and cardiovascular septal defects among others. 5 In familial cases, an autosomal dominant inheritance pattern has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…5 Associated conditions include vertebral defects, anal atresia, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities (VACTERL), various urogenital abnormalities, and cardiovascular septal defects among others. 5 In familial cases, an autosomal dominant inheritance pattern has been identified. 6 Although crossed fused renal ectopia is often discovered incidentally while investigating other genitourinary issues, approximately half of all patients experience complications, such as hydronephrosis, nephrolithiasis, and frequent urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%